Pengaruh Implementasi Satu Kemenkeu sebagai Pengendalian Internal dalam Sistem Informasi Akuntansi, dan Kompetensi SDM Terhadap Efisiensi Administrasi pada KPPBC TMPC Sumbawa - Selfi Pebrianti; Ahmad Jibrail (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to analyze the influence of Satu Kemenkeu platform implementation as an internal control mechanism in the Accounting Information System (AIS) and human resource competency on administrative efficiency at KPPBC TMPC Sumbawa. The research employed a quantitative approach with total sampling of 33 employees. Data were collected through online questionnaires using a 5-point Likert scale and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) via SmartPLS software. The results indicate that Satu Kemenkeu implementation has a positive and significant effect on administrative efficiency (path coefficient = 0.534; T-statistic = 2.675; p-value = 0.007), whereas human resource competency has a positive but insignificant effect (path coefficient = 0.308; T-statistic = 1.644; p-value = 0.100). Theoretically, this study extends public-sector AIS and internal control literature by demonstrating that an integrated digital control platform can become the dominant mechanism for administrative efficiency in a standardized public bureaucracy. The findings also refine the role of human resource competency by showing that competency may function as a basic enabling condition rather than a differentiating factor when work procedures and information controls are strongly embedded in the system. Practically, KPPBC TMPC Sumbawa should prioritize system optimization, user compliance, and advanced feature utilization while maintaining continuous competency development.